Phenolic profile by HPLC-ESI-MS/MS and enzymatic inhibitory effect of Bryophyllum delagoense. Issue 22 (18th November 2021) - Katrucha, Edenize Maria; Lopes, Jéssica; Paim, Milena; dos Santos, Júlia Candiani; Siebert, Diogo Alexandre; Micke, Gustavo Amadeu; Vitali, Luciano; Alberton, Michele Debiasi; Tenfen, Adrielli
Abstract: Bryophyllum delagoense (Eckl. & Zeyh.) Druce, native to Madagascar, is popularly known as "abyssian cactus" and popularly used in folk medicine as an analgesic and healing agent. The study methodology was divided into the phytochemical study: fractionation and identification of phenolic compounds by HLPC-ESI-MS/MS from the methanolic extract (ME), and fractions (DCMF and EAF) of leaves of B. delagoense, and biological activity with acetylcholinesterase and α-glucosidase inhibition of extracts and fractions by in vitro enzymatic techniques. Twenty-seven phenolic compounds were identified, being the highest concentration of syringic acid (87.848 mg g −1 ). The DCMF fraction showed the best biological activity for inhibition of α-glucosidase enzyme (0.125 mg mL −1 ). Graphical Abstract: